2021
DOI: 10.1021/acs.est.0c04952
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bioavailability and Microbial Biodegradation of Polystyrene in an Enrichment Derived from the Gut Microbiome of Tenebrio molitor (Mealworm Larvae)

Abstract: As the global threat of plastic pollution has grown in scale and urgency, so have efforts to find sustainable and efficient solutions. Research conducted over the past few years has identified gut environments within insect larvae, including Tenebrio molitor (yellow mealworms), as microenvironments uniquely suited to rapid plastic biodegradation. However, there is currently limited understanding of how the insect host and its gut microbiome collaborate to create an environment conducive to plastic biodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 59 publications
5
69
0
2
Order By: Relevance
“…However, the weight loss is very low compared to the direct consumption of PS by insect larvae. Previous researches have reported that plastic-degrading microorganisms demonstrate expedited degradation within the insect gut environment (Przemieniecki et al, 2020;Brandon et al, 2021). This phenomenon implies that the insect host may play a role in the plastic biodegradation process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the weight loss is very low compared to the direct consumption of PS by insect larvae. Previous researches have reported that plastic-degrading microorganisms demonstrate expedited degradation within the insect gut environment (Przemieniecki et al, 2020;Brandon et al, 2021). This phenomenon implies that the insect host may play a role in the plastic biodegradation process.…”
Section: Discussionmentioning
confidence: 98%
“…G. mellonella larvae have been shown that they retain the capacity to metabolize polyethylene when their gut microbiome activity is suppressed (Kong et al, 2019). In addition, Brandon et al (2021) and Tsochatzis et al (2021) provide evidence that insect larvae secrete emulsifying factors or enzymes that mediate plastic biodegradation. These studies indicate that using insect larvae to degrade plastic is a complex system in which the larvae host and its gut microbiome collaborate to work.…”
Section: Discussionmentioning
confidence: 99%
“…YT2 from the guts of T. molitor larvae. Brandon et al [ 22 ] identified eight unique gut microorganisms associated with PS biodegradation including Citrobacter freundii , Serratia marcescens , and Klebsiella aerogenes . Woo et al [ 32 ] isolated a PS-degrading strain Serratia sp.…”
Section: Resultsmentioning
confidence: 99%
“…Among these insect larvae, three species have been studied further, including the yellow mealworm (larvae of Tenebrio molitor L.), the greater wax moth (larvae of Galleria mellonella L.), and the superworm (larvae of Zophobas atratus Fab.). The literature and our studies have shown that all three insects can eat and degrade PS [ 16 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of microbes in this process is crucial as explained by (Zhang et al, 2021). Even plastic biodegradation can be accelerated by mealworm and their gut microbiome (Brandon et al, 2021). Also, Peng et al (2019) demonstrated that Tenebrio species and their gut microbes were able to biodegrade polystyrene.…”
Section: Organic Side Streams To Rear Insectsmentioning
confidence: 99%